The impact of sleep duration on physical activity in daily life in patients with idiopathic pulmonary fibrosis - Silva, Humberto; Mantoani, Leandro C.; Aguiar, Wagner F.; Gonçalves, Aline F. L.; da Silva, Thatielle G.; Zamboti, Camile L.; Ribeiro, Marcos; Probst, Vanessa S.; Pitta, Fabio; Camillo, Carlos A. [UNESP] (Taylor & Francis, 2023)
Background: Despite the high prevalence of sleep disturbances in idiopathic pulmonary fibrosis (IPF), the relationship between physical activity in daily life (PADL) and sleep in this population remains unclear Objectives: Investigate the impact of sleep on different domains of PADL in IPF and characterize their PADL profile Methods: Sixty-seven participants (thirty-three with IPF and thirty-four healthy subjects [control group]) were included. The subjects underwent assessments of pulmonary function, exercise capacity, respiratory and peripheral muscle strength, PADL, sleep, dyspnea, and health-related quality of life. PADL and sleep measures were assessed using an activity monitor (Actigraph®, wGT3x-BT). Associations between sleep and PADL were done using correlation and regression models. Results: In the IPF, sleep duration at night associated significantly with step counts, sedentary, light, and moderate-to-vigorous physical activity (MVPA) (−0.82 ≤ R ≤ 0.43; p < .05 for all). Lung function and sleep partially explained PADL variables (0.19 ≤ R2 ≤ 0.65, p < .05 for all). Compared to controls, the IPF subjects presented lower step counts, less time spent in MVPA, standing position, and more time spent in lying position (p < .05, for all) Conclusions: Sleep duration is associated with PADL in IPF. The PADL profile of patients is worse than in control subjects.
Keywords: actigraphy; Idiopathic pulmonary fibrosis; physical activity in daily life; sleep